Structure of the Bacillus subtilis hibernating 100S ribosome reveals the basis for 70S dimerization - Beckert, Bertrand (EMBO J, 2017)
Under stress conditions, such as nutrient deprivation, bacteria enter into a hibernation stage, which is characterized by the appearance of 100S ribosomal particles. In Escherichia coli, dimerization of 70S ribosomes into 100S requires the action of the ribosome modulation factor (RMF) and the hibernation‐promoting factor (HPF). Most other bacteria lack RMF and instead contain a long form HPF (LHPF), which is necessary and sufficient for 100S formation. While some structural information exists as to how RMF and HPF mediate formation of E. coli 100S (Ec100S), structural insight into 100S formation by LHPF has so far been lacking. Here we present a cryo‐EM structure of the Bacillus subtilis hibernating 100S (Bs100S), revealing that the C‐terminal domain (CTD) of the LHPF occupies a site on the 30S platform distinct from RMF. Moreover, unlike RMF, the Bs HPF‐CTD is directly involved in forming the dimer interface, thereby illustrating the divergent mechanisms by which 100S formation is mediated in the majority of bacteria that contain LHPF, compared to some γ‐proteobacteria, such as E. coli.